Pengaruh Variasi Temperatur Tempering terhadap Kekerasan Baja JIS SUP 9A pada Mata Pisau - Nanda Aulia Fadli; Adi Saputra Ismy; Irwin Syahri Cebro (Politeknik Negeri Lhokseumawe, 2022)
The effect of tempering temperature variations on the hardness of the blade has been carried out on SUP 9A leaf spring steel material. The tempering process was carried out at temperatures of 300°C, 400°C, and 500°C with a holding time of 15 minutes and cooled in free air. Specimens without heat treatment and tempering results were tested for hardness using the Rockwell hardness test method and microstructure analysis using an optical microscope. From the results of the study, it was found that the hardness value obtained on the raw material specimen without heat treatment obtained a hardness value of 60.50 HRC, while the tempering temperature variation obtained the hardness value on specimen B (tempering temperature 300°C) of 66.90 HRC, specimen C (tempering temperature 400°C) of 64.70 HRC, while specimen D (tempering temperature 500°C) obtained a hardness value of 65.80 HRC. From the results of the specimen hardness test, the hardness value after heating was higher than the hardness value without heating treatment. Microstructural analysis shows that the higher the given temperature, the larger the grain of the steel structure looks. Without heat treatment the microstructure of the specimen is an irregular black bainite. Meanwhile, by heat treatment, the microstructure of the specimen is irregular black martensite.